2020
DOI: 10.3390/ijerph17041352
|View full text |Cite
|
Sign up to set email alerts
|

Extending a Conceptual Framework for Junior Doctors’ Career Decision Making and Rural Careers: Explorers versus Planners and Finding the ‘Right Fit’

Abstract: This study uses data from a Rural Clinical School of Western Australia (RCSWA) and WA Country Health (WACHS) study on rural work intentions among junior doctors to explore their internal decision-making processes and gain a better understanding of how junior doctors make decisions along their career pathway. This was a qualitative study involving junior doctor participants in postgraduate years (PGY) 1 to 5 undergoing training in Western Australia (WA). Data was collected through semi-structured telephone inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…It is highly simplistic to assume that having these rural training experiences or early declarations of a rural intent/preference guarantees large numbers will stay rurally. The high level of uncertainty of their practice location can be seen as both a negative and a positive-there remains a large pool who are continually reassessing their career decisions and this includes those considering rural practice [43]; however, many may be open to the idea of rural practice but eventually decide otherwise, as competing interests, such as family needs, take preference [44]. This large pool of 'fence sitters' thus highlights the ongoing importance of maximising positive experiences amongst junior doctors of factors known to both pull towards and retain them in rural practice, whilst minimising negative experiences of factors known to push them away from rural practice [37,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is highly simplistic to assume that having these rural training experiences or early declarations of a rural intent/preference guarantees large numbers will stay rurally. The high level of uncertainty of their practice location can be seen as both a negative and a positive-there remains a large pool who are continually reassessing their career decisions and this includes those considering rural practice [43]; however, many may be open to the idea of rural practice but eventually decide otherwise, as competing interests, such as family needs, take preference [44]. This large pool of 'fence sitters' thus highlights the ongoing importance of maximising positive experiences amongst junior doctors of factors known to both pull towards and retain them in rural practice, whilst minimising negative experiences of factors known to push them away from rural practice [37,43].…”
Section: Discussionmentioning
confidence: 99%
“…The high level of uncertainty of their practice location can be seen as both a negative and a positive-there remains a large pool who are continually reassessing their career decisions and this includes those considering rural practice [43]; however, many may be open to the idea of rural practice but eventually decide otherwise, as competing interests, such as family needs, take preference [44]. This large pool of 'fence sitters' thus highlights the ongoing importance of maximising positive experiences amongst junior doctors of factors known to both pull towards and retain them in rural practice, whilst minimising negative experiences of factors known to push them away from rural practice [37,43]. The importance of continued opportunities for postgraduate rural training pathways to support growing the rural workforce has been demonstrated amongst one specialty group (international medicine) [45].…”
Section: Discussionmentioning
confidence: 99%
“…It suited me.” pg 3 [ 58 ] “So, I guess at this point I want to be a generalist. I like a bit of everything, it keeps it interesting, it keeps it fresh” pg 6 [ 37 ] 1.2.2 Career challenges 2.2.2 Career and specialisation challenges “Whilst I enjoy the rural lifestyle and experience. As a new graduate, I am limited with opportunities to further my career … ..…”
Section: Resultsmentioning
confidence: 99%
“…“So, I guess at this point I want to be a generalist. I like a bit of everything, it keeps it interesting, it keeps it fresh” pg 6 [ 37 ]…”
Section: Resultsmentioning
confidence: 99%
“…As such, the opinions of early‐career doctors may differ from those of medical students. One qualitative study of 21 Western Australian doctors (mostly limited to 3 years post‐graduation from a rural clinical school) identified that early‐career decision‐making about rural work is complex and dynamic 8 . With this background in mind, we sought to explore the attractors and barriers for early‐career doctors to pursue rural pathways after graduating from medical school.…”
Section: Introductionmentioning
confidence: 99%